PERHITUNGAN HARGA POKOK PRODUKSI CELURIT MADURA: KOMPARASI METODE FULL COSTING VS PEMILIK USAHA - Rudistira, Ricko Zakaria; Sula, Atik Emilia (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to compare the calculation of the cost of production of the Takabuan celurit, one type of Madura celurit, based on the full costing method and business owner-style calculations. This research uses a qualitative method with a case study approach carried out on several blacksmiths engaged in sickle production in Paterongan village. The research results show indications of differences in the results of calculating the cost of goods produced between the full costing method and calculations carried out by craftsmen. The results of calculations using the full costing method produce a higher cost of production compared to the calculations of celurit craftsmen. This is because in the full costing method all cost elements attached to the product are traced in more detail than in the craftsman's version. Full costing can identify costs in detail, both raw material costs, fixed factory overhead costs and variable factory overhead costs as well as labor costs. Full costing calculations can identify actual costs compared to calculations according to craftsmen